LIN28 Is Selectively Expressed by Primordial and Pre-Meiotic Germ Cells in the Human Fetal Ovary - Childs, Andrew J. (Mary Ann Liebert, Inc., 2012)
Germ cell development requires timely transition from primordial germ cell (PGC) self-renewal to meiotic differentiation. This is associated with widespread changes in gene expression, including downregulation of stem cell–associated genes, such as OCT4 and KIT, and upregulation of markers of germ cell differentiation and meiosis, such as VASA, STRA8, and SYCP3. The stem cell–expressed RNA-binding protein Lin28 has recently been demonstrated to be essential for PGC specification in mice, and LIN28 is expressed in human germ cell tumors with phenotypic similarities to human fetal germ cells. We have therefore examined the expression of LIN28 during normal germ cell development in the human fetal ovary, from the PGC stage, through meiosis to the initiation of follicle formation. LIN28 transcript levels were highest when the gonad contained only PGCs, and decreased significantly with increasing gestation, coincident with the onset of germ cell differentiation. Immunohistochemistry revealed LIN28 protein expression to be germ cell–specific at all stages examined. All PGCs expressed LIN28, but at later gestations expression was restricted to a subpopulation of germ cells, which we demonstrate to be primordial and premeiotic germ cells based on immunofluorescent colocalization of LIN28 and OCT4, and absence of overlap with the meiosis marker SYCP3. We also demonstrate the expression of the LIN28 target precursor pri-microRNA transcripts pri-LET7a/f/d and pri-LET-7g in the human fetal ovary, and that expression of these is highest at the PGC stage, mirroring that of LIN28. The spatial and temporal restriction of LIN28 expression and coincident peaks of expression of LIN28 and target pri-microRNAs suggest important roles for this protein in the maintenance of the germline stem cell state and the regulation of microRNA activity in the developing human ovary.